2016
DOI: 10.1007/978-1-4939-3684-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Microwell-Based Live Cell Imaging of NK Cell Dynamics to Assess Heterogeneity in Motility and Cytotoxic Response

Abstract: NK cell heterogeneity has primarily been studied either on the population level, measuring average responses, or on the single cell level by flow cytometry, providing static snapshots. These approaches have certain drawbacks, not enabling dynamic observations of single cells over extended periods of time. One of the primary limitations of single cell imaging has been throughput; it has been challenging to collect data for many cells due to their dynamic nature and migrating out of the field of view. Spatially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Calcein labels the cytosol of viable cells making them clearly detectable by fluorescence microscopy. Upon cell death Calcein green leaks out making it possible to monitor NK cell induced target cell death through loss of fluorescence 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Calcein labels the cytosol of viable cells making them clearly detectable by fluorescence microscopy. Upon cell death Calcein green leaks out making it possible to monitor NK cell induced target cell death through loss of fluorescence 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, very fast migratory events, such as Natural Killer (NK) cell 45 and Dendritic Cell (DC) 46 movement, may be missed by imaging every 15 min. However, imaging intervals can be optimized to study the specific cell-cell interactions of interest, and the ability to image in 3 dimensions through z-stacks allows the assessment of 3D cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…Time lapse cinematography indicated that, in NK modes without antibody, there is heterogeneity in serial killing. Some cells within the effector cell populations bound to targets without killing them while the cytotoxic cells killed 1, 2, 3, or even up to 5-7 times [16,21]. Microchip experiments also indicated cellular differences in killing when the NK cells are in ADCC mode.…”
Section: Introductionmentioning
confidence: 98%